Digital Governance And The Right To Privacy: A Comparative Analysis Of AI Regulation In Southeast Asia And The European Union - Muh Habibulloh (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study investigates the evolving regulatory landscape of artificial intelligence (AI) and personal data protection through a comparative legal analysis between Southeast Asia (ASEAN) and the European Union (EU). As AI technologies increasingly permeate public governance, economic systems, and everyday decision-making, they introduce complex legal and ethical challenges related to algorithmic accountability, privacy rights, and data security. The EU, exemplified by the General Data Protection Regulation (GDPR) and the proposed Artificial Intelligence Act, has developed a rights-based, precautionary regulatory model rooted in fundamental freedoms and democratic oversight. In contrast, ASEAN member states display considerable diversity in legal frameworks, enforcement capacities, and normative approaches—often prioritizing innovation, digital competitiveness, and pragmatic governance over stringent privacy safeguards. Employing a doctrinal and comparative methodology, this study analyzes statutes, institutional structures, and regional policy initiatives such as the ASEAN Framework on Digital Data Governance. The findings reveal significant regulatory asymmetries but also emerging areas of convergence. The study concludes by advocating for enhanced regional cooperation, capacity-building, and the adoption of adaptive, risk-based legal frameworks that align technological development with human rights standards. These insights contribute to the broader global discourse on ethical digital governance and the achievement of the UN Sustainable Development Goals (SDGs), particularly Goal 16 on peace, justice, and strong institutions.